Hydroxyurea appears beneficial in patients with beta-thalassaemia major and intermedia (Faculty of Medicine Universitas Indonesia, 2007)
Patients with severe inherited β-globin chain disorders may have milder illness if they produce high levels of fetal hemoglobin (HbF). Hydroxyurea (HU) has been shown to enhance HbF levels in patients with sickle cell disease and may be useful in β-thalassemias. We administered HU to 13 patients with β-thalassemia intermedia or major, including 6 splenectomized patients. The patients received escalating doses (10 to 25 mg/kg/d) of HU for around 2 years (median: 21 months, range: 8 - 55 months). Eleven patients responded with an increase in the pre-transfusion HbF levels, from a base line median of 8.0% (2.5 - 61.3%) to 28.0% (6.6 - 49.2%) and 40.7% (4.8 - 72.3%) at 3 months and 18 months post-HU, respectively. A concomitant increment in median hemoglobin levels was noted at 1, 3 and 18 months of HU therapy. Six of 7 transfusion-dependent patients who had an increment of HbF (one with β-thalassemia major) also had reduced transfusion requirement over the 2-year period of HU therapy. Response to HU was also shown by a reduction in spleen size. Apart from oral ulcers that resolved upon dose reduction of HU, no significant toxicity was noted. We conclude that increased HbF production in β-thalassemia patients, with an improvement in erythropoiesis, can be achieved using HU with minimal toxicity. (Med J Indones 2007; 16:78-83) Keywords: fetal hemoglobin (HbF), erythropoiesis, toxicity